A two-year retrospective study of infants with Erb-Duchenne's palsy at a tertiary centre in Rajasthan, India - Hasabe, Rakesh Appasaheb; Diwane, Dnyaneshwar S.; Chandawar, Sushant S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Brachial plexus injury (BPI) has prevalence of between 0.5 and 4.4/1000 live births. It is commonly believed to be attributed to extensive lateral traction during difficult neck delivery. This paper aims to look at one aspect of birth injuries, Erb-Duchenne palsy, its incidence and contributing factors. Methods: All infants sustaining Erb-Duchenne palsy during birth were identified at Department of OBGY, NIMS Hospital, Jaipur. The notes of the infants and mothers were reviewed. Special attention was given to the known risk factors for birth trauma such as ethnicity, parity, antenatal care, history of diabetes etc. Results: During the two-year period 2013 to 2015, there were 6 infants diagnosed with Erb-Duchenne palsy, giving an incidence of 0.79 in 1000 live births. Out of six, four were primigravidae. All pregnancies were singleton, cephalic/vertex undergoing vaginal deliveries; none required forceps or ventouse deliveries. The mean infant birthweight was 4.378 kg with a median value of 4.48 kg (range 3.51-4.78). Four infants were classified as macrosomic i.e. birthweights greater than 4 kg, four infants had birthweights of 4 kg to 5 kg; none weighed over 5 kg. Three of the deliveries were documented as difficult shoulder delivery/shoulder dystocia. Five of the infants had APGAR scores that were less than seven. Conclusions: This study suggested that Erb-Duchenne palsy is strongly associated with fetal macrosomia and shoulder dystocia. Diabetes was not significant in causing macrosomia as only single mother was found diabetic. Fetal macrosomia contributed to shoulder dystocia in the majority of cases.